مدى اختصاص البرلمان الجزائري في وضع قواعد التقسيم الانتخابي لانتخاب أعضاء المجلس الشعبي الوطني - شامي, رابح (Université de M'sila, 2019)
ملخص: تعد البرلمانات المعبر الحقيقي عن إرادة الشعب، من خلال اختصاصها لوحدها بوضع القانون، ولما اقتضت الظروف توزيع اختصاص تنظيم شؤون المجتمع بين السلطتين التشريعية والتنفيذية، صار البرلمان لا يمكنه وضع القانون إلا بناء على نص من الدستور، وهو ما يطرح التساؤل حول مدى اختصاص البرلمان الجزائري بوضع قانون تقسيم الدوائر الانتخابية وعدد مقاعدها لانتخاب أعضاء المجلس الشعبي الوطني. Resume Parliaments are real expression about the will of people through their own specialization by placing the law but when the specialization of organizing affairs of society distributes between the two authorities legislation and executive the parliament is not able to place a law without a text from the constitution. This take us to ask a question about how extent the Algerian parliament specialization place a law about electoral distrid division and their number of seats to vote nation people’s assembly.
Keywords: برلمان، قانون، تقسيم، انتخاب parliament, law, division, election